LIM Domain Only 2 Regulates Endothelial Proliferation, Angiogenesis, and Tissue Regeneration - Shu Meng; Gianfranco Matrone; Jie Lv; Kaifu Chen; Wing Tak Wong; John P. Cooke (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundLIM domain only 2 (LMO2, human gene) is a key transcription factor that regulates hematopoiesis and vascular development. However, its role in adult endothelial function has been incompletely characterized. Methods and ResultsIn vitro loss‐ and gain‐of‐function studies on LMO2 were performed in human umbilical vein endothelial cells with lentiviral overexpression or short hairpin RNA knockdown (KD) of LMO2, respectively. LMO2 KD significantly impaired endothelial proliferation. LMO2 controls endothelial G1/S transition through transcriptional regulation of cyclin‐dependent kinase 2 and 4 as determined by reverse transcription polymerase chain reaction (PCR), western blot, and chromatin immunoprecipitation, and also influences the expression of Cyclin D1 and Cyclin A1. LMO2 KD also impaired angiogenesis by reducing transforming growth factor‐β (TGF‐β) expression, whereas supplementation of exogenous TGF‐β restored defective network formation in LMO2 KD human umbilical vein endothelial cells. In a zebrafish model of caudal fin regeneration, RT‐PCR revealed that the lmo2 (zebrafish gene) gene was upregulated at day 5 postresection. The KD of lmo2 by vivo‐morpholino injections in adult Tg(fli1:egfp)y1 zebrafish reduced 5‐bromo‐2′‐deoxyuridine incorporation in endothelial cells, impaired neoangiogenesis in the resected caudal fin, and substantially delayed fin regeneration. ConclusionsThe transcriptional factor LMO2 regulates endothelial proliferation and angiogenesis in vitro. Furthermore, LMO2 is required for angiogenesis and tissue healing in vivo. Thus, LMO2 is a critical determinant of vascular and tissue regeneration.